Clinical features of chronic primary pain in individuals presenting painful temporomandibular disorder and comorbidities - dos Santos Proença, Juliana [UNESP]; Baad-Hansen, Lene; do Vale Braido, Guilherme Vinícius [UNESP]; Campi, Letícia Bueno [UNESP]; de Godoi Gonçalves, Daniela Aparecida [UNESP] (Wiley, 2024)
Background: The diagnosis of chronic primary pain (CPP), according to the recently released International Classification of Disease (ICD-11) criteria, refers to conditions with complex aetiologies. CPP is characterized by specific clinical features such as generalized sensory hypersensitivity and widespread pain, and is associated with functional disability and emotional distress. Objective: This study investigated clinical features of CPP in individuals with painful temporomandibular disorders (TMD) and comorbidities (fibromyalgia, migraine and/or tension-type headache). Methods: This cross-sectional study was conducted with a sample of 129 individuals. Painful TMD, fibromyalgia and primary headaches were evaluated based on well-established international criteria. Generalized sensory hypersensitivity was assessed using psychophysical tests. Symptoms of anxiety and depression were assessed by the Generalized Anxiety Disorder-7 and Patient Health Questionnaire-9. The Central Sensitization Inventory was applied to assess central sensitization-related symptoms and the Pittsburg Sleep Quality Index to evaluate the quality of sleep. The presence of widespread pain was assessed using a body map. The sample was stratified into three groups: control (n = 25), TMD—painful TMD only (n = 35) and TMD + Cm—painful TMD and comorbidities (n = 69). Statistical analysis was performed using one-way ANOVA, chi-squared test and ANCOVA, considering gender as a covariate (α =.05). Results: Compared to controls, individuals presenting painful TMD and comorbidities showed lower pressure pain thresholds in all evaluated areas (p ≤.012) and a higher number of painful areas in the body (p =.001). They presented more symptoms of anxiety (p =.040) and depression (p =.018), and a higher score in the Central Sensitization Inventory (p ≤.006) than the other groups. Conclusion: Individuals with painful TMD and comorbidities presented more clinical features of CPP compared to those affected by TMD only.
Keywords: central nervous system sensitization; chronic pain; comorbidity; fibromyalgia; headache; temporomandibular joint disorders